Analysis of Landslide Potential Based on Slopes And Rock Weathering Levels in The Mamampang Area, Tombolopao District, Gowa Regency, South Sulawesi Province - Dwita Safirah; Busthan Azikin (CV Insight Publisher, 2025)
The Mamampang area is composed of the rocks of the Lompobattang Volcano with the dominance of tufa lithology which is fragile and easily weathered. Morphologically, the study area shows the shape of hills to mountains with steep slopes – very steep, so it has a high vulnerability to the movement of soil masses. This study aims to analyze the potential for landslides based on the parameters of the slope and the rate of rock weathering. Slope geometry measurements were carried out using geological compasses and roll meters, then analyzed with the Bermana (2006) classification, while the rate of rock weathering was determined based on the classification of Irfan and Dearman (1978). The results showed that most slopes have a slope angle between 40°–52° with a slope percentage of 50–129% (steep to very steep category), and the weathering rate is at degrees IV–VI (strong weathered to residual soil). The condition of the tufa lithology that has undergone advanced weathering, combined with steep morphology, land use on steep slopes, and intense rainfall, is the dominant factor determining slope instability. The potential for landslides in the Mamampang area is categorized as very high, so mitigation efforts based on geology engineering are needed through land use management and strengthening of slope cover vegetation.